Scratch‐Healing Surface‐Attached Coatings from Metallo‐Supramolecular Polymer Conetworks. Issue 3 (28th December 2020) - Mugemana, Clément; Martin, Anouk; Grysan, Patrick; Dieden, Reiner; Ruch, David; Dubois, Philippe
Abstract: Self‐healing polymer coatings have gained increased attention as a pathway for regenerating the inherent properties of surface following mechanical, physical or chemical damages. In most cases, the adhesion between the polymer coating layer and the substrate is driven by physical interactions. For some applications, immersing the polymer coating under water or exposing the coating to organic solvent vapors will undoubtedly lead to the coating delamination. One way to circumvent this issue is to attach the coating to the substrate via covalent bonds. However, this process will impede the self‐healing feature of the polymer coating due to the confinement of the volume change of the polymer to one dimension. Herein, surface‐attached metallo ‐supramolecular polymer conetwork coatings are reported. The ability of the polymer conetworks to swell in organic solvent while maintaining their dimensional stability combined with reversible supramolecular cross‐links based on metal complexes enables the design of scratch‐healing polymer coatings. These metallo ‐supramolecular polymer conetworks are prepared in a three‐step UV‐initiated polymerization reaction starting from the poly(pentafluorophenyl acrylate)‐ l ‐polydimethylsiloxane (PPFPA‐ l ‐PDMS)‐activated ester covalently attached to the substrate. Reacting the polymer conetwork coating with the 4‐(2‐aminoethyl)pyridine and cross‐linking the pyridine phases with ZnCl2 lead to the poly( N ‐(2(pyridin‐4‐yl)ethyl)acrylamide‐Zn(II))‐ l ‐polydimethylsiloxane (PNP4EA‐Zn(II)‐ l ‐PDMS) polymer conetwork coatings with scratch‐healing ability. Abstract : Surface‐attached coatings based on metallo ‐supramolecular polymer conetworks are presented. These coatings are prepared in a three‐step UV‐initiated polymerization process. The reversible metal complexes interactions combined with the ability of the polymer conetwork to swell in organic solvent while maintaining its dimensional stability are used to trigger the scratch‐healing property of the polymer coating.